Micropropagação de Hyptis ramosa Pohl ex Benth. (Lamiaceae) - Sousa, Flávia Pereira de (2015)
Hyptis ramosa Pohl ex Benth (Lamiaceae) is native and endemic to the semi-arid northeast, with its unknown phytochemical constitution so far. Considering the pharmacological importance of the species of this family, the development of forms of propagation and in vitro culture can contribute to the inclusion of these species in sustainable production systems and the conservation of the same. Thus, the objective of this work was to study the in vitro propagation of the species H. ramosa, through direct organogenesis and callus formation, and the biochemical characterization of the obtained calluses, thus allowing the establishment of strategies for their conservation and sustainable use. To this, H. ramosa seeds were disinfected and established in medium MS / 2 culture. In the multiplication phase was tested the influence of cytokinins BAP, CIN and TDZ on different explants. The obtained shoots were individualized and transferred to MS / 2 medium containing different concentrations of auxin IBA and activated carbon for rooting them. Regenerated and rooted in vitro microplants were subjected to pre-acclimatization in different cultivation container closure and then were transferred to ex vitro conditions in commercial substrate Plantmax® being quantified plant survival rate at 30 days after transfer. For callus induction, we used explants and different concentrations of 2,4-D and BAP, determining the growth curve from the fresh weight of callus until the 28th day of cultivation, at intervals of seven days. Concurrent with obtaining the growth curve it is quantified in calluses obtained the total soluble sugar content, reducing sugar and crude protein. The in vitro propagation of H. ramosa is possible using the nodal segment as a source of explants in MS medium supplemented with BAP. In vitro rooting occurs, even in free auxin. The species showed survival of 100%, regardless of the day of pre-acclimatization phase. For callus induction the best explant is the nodal segment, and the combination of 2.4-D and BAP favor the formation of the same. The callus growth curve showed quadratic behavior with two different phases and biochemical analysis showed the maximum level of total soluble sugars, reducing sugars and crude protein at 14 °, 21 ° and 14 ° days, respectively.